Interpersonal functions in Greta Thunberg’s “civil society for rEUnaissance” speech - Stefanny Lauwren (English, 2020)
Greta Thunberg delivered a speech entitled “You’re Acting Like Spoiled, Irresponsible Children” to influential figures in Europe through the “Civil Society for renaissance” event, in which she was personally invited by the president of the organizer, Luca Jahier. Through her speech, she managed to convince the European Union to pledge to spend billions of Euro to combat the climate crisis. This study aims to discover how interpersonal metafunction is used in the speech and what functions are revealed through Fairclough’s Critical Discourse Analysis and Hallidayan Systemic Functional Grammar. The data, consisting of seventy-one independent clauses, were taken from Thunberg’s book which consists of her speech transcription, titled “No One Is Too Small to Make a Difference”. The research discovers that through the use of mood, modality, and pronouns, Thunberg conveys her view on her relationship with the audience as victim and perpetrator, and the one who holds responsibility and takes the blame.